MEMERDEKAKAN LAPANGAN MERDEKA BARU DI KOTA MEDAN - Thierry Henry; Rudy Surya (Jurusan Arsitektur dan Perencanaan, 2023)
Merdeka Square in Medan City, the capital city of North Sumatra Province, with an area of 48,877 square meters has experienced a degradation pattern of space use or function conversion. Initially the Merdeka field was a Green Open Space (RTH) for the city of Medan as well as the lungs of the city and the heart of the city of Medan. In addition to the decline in the function of space, there is also a loss of image due to the development being carried out without regard to the main function and role of the field, which is an issue of significance that will be raised so that it can have a positive impact on the surrounding community of the area. So it is necessary to develop Merdeka Square by returning Green Open Spaces (RTH) which have passed local regulations, developing programs that can restore lost historical and cultural values in the area. Urban Acupuncture can be the answer to the problems that exist on Merdeka Square, with minimal changes but can have a big impact on Merdeka Square itself. The method used for the design is